2003
DOI: 10.1111/1467-9493.00164
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration Across Borders: Moving Beyond Positionality

Abstract: Discussions about collaborative spaces in postcolonial feminist and geographical analyses have often hinged on questions of positionality, reflexivity and identity, largely in relation to the politics of representation. Such approaches have often led to an impasse, especially in fieldwork-based feminist research, where reflexivity has mainly focused on examining the identities of the individual researcher rather than on the ways in which those identities intersect with institutional, geopolitical and material … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(66 citation statements)
references
References 13 publications
0
63
0
Order By: Relevance
“…A deeper future enquiry and a critical reflection into the epistemology of the EJAtlas should examine the politics and strategies of representation and question voices and authorship, however this is a task that must be reserved for its own article as we do not have space to engage fully with the range of issues that have presented themselves here. This could provide a deeper assessment of whether the EJAtlas is a repository of stories and struggles that is accessible to people with a sociopolitical agenda that could transform "power hierarchies embedded in research" (Nagar and Ali 2003).…”
Section: Discussionmentioning
confidence: 99%
“…A deeper future enquiry and a critical reflection into the epistemology of the EJAtlas should examine the politics and strategies of representation and question voices and authorship, however this is a task that must be reserved for its own article as we do not have space to engage fully with the range of issues that have presented themselves here. This could provide a deeper assessment of whether the EJAtlas is a repository of stories and struggles that is accessible to people with a sociopolitical agenda that could transform "power hierarchies embedded in research" (Nagar and Ali 2003).…”
Section: Discussionmentioning
confidence: 99%
“…But while Davidson et al's collaborative practice identified all the authors as equal collaborators, our practices of authorship more closely resemble Richa Nagar's work with Farah Ali and the Sangatin women's collective (Nagar et al 2003). Here Nagar and Ali coauthored the work, and the women's collective participated in consultation with them, streamlining the writing process while allowing for input from the group for each new draft.…”
Section: Collaborative Authorship Among Instructor(s) and Studentsmentioning
confidence: 73%
“…Here Nagar and Ali coauthored the work, and the women's collective participated in consultation with them, streamlining the writing process while allowing for input from the group for each new draft. All three are examples of collaborative processes and different expressions of a scholarly teaching and research praxis influenced by feminist and postcolonial partnerships (see Boyer 1990;Hutchings and Shulman 1999;Nagar et al 2003;Medley, Zhou, and Condon 2006). The collaborative nature of the class extended well beyond the confines of the classroom and even the work of this article as students and professor continue to dialogue about qualitative methods more than four years later.…”
Section: Collaborative Authorship Among Instructor(s) and Studentsmentioning
confidence: 91%
“…As Nagar and Ali (2003) intimate, moving between and across subject positions in research is context and path dependent. It happened to be that one researcher was already in the Oxford Tavern's music scene.…”
Section: Negotiating Research Methods -A Pragmatic Approachmentioning
confidence: 99%